Handbook of essential oils : science, technology, and applications - Baser, K. H. C. [ (Kemal Husnu Can)]; Buchbauer, Gerhard (CRC Press/Taylor & Francis, 2010)
The society looks to science to document health choices and the oils do not disappoint. This book covers various aspects of essential oils from chemistry, pharmacology, and biological activity, to production and trade, to uses and regulation. It provides information related to the development, use, and marketing of essential oils.